SOFTENING OF HARDENED MEDIUM-CARBON STEEL DURING HEATING - I. O. Vakulenko (Nauka ta progres transportu, 2019)
Purpose. The work is aimed to clarify the softening mechanism during the heating of martensite hardened carbon steel, which is of practical importance, especially in the development of the production technology of rolled products with different levels of hardening. Methodology. The samples after martensite hardening were tempered at the temperatures of 300-500˚С. The microstructure was investigated under the electron microscope. Thin foils were made using the Bolman and tweezer methods in chlorous-acetic solution and Morris reagent. Phase distortions of crystalline lattice were determined by the methods of X-ray structural analysis, using the diffractometer. The cold-worked layer of metal after grinding was removed by electrolytic dissolution. Tensile strength brake of the metal was determined using the tensile diagrams of samples using the Instron type machine. Microhardness was measured using the PMT-3 device with indentation load 0.49 N. Findings. When heating the hardened steel to a temperature of 300˚C, the softening effect is mainly related to the rate of reduction of the accumulated as a result of martensitic transformation, density of the crystalline structure defects. The total result is caused by the development of dislocations recombination and strengthening because of the emergence of additional number of cementite particles during the martensitic crystals decomposition. Starting from the heating temperatures of 400˚C and above, the development of polygonization processes in the ferrite is accompanied by the emergence of additional sub-boundaries, which enhance the effect of metal strengthening. With increase in the heating temperature of the hardened steel, the level of strength properties is determined by the progressive softening from the decrease in carbon atoms saturation degree of the solid solution, dislocations density and increase in the size of cementite particles over the effect of strengthening from hindering of mobile dislocations by carbon atoms and the emergence of additional sub-boundaries. Originality. For the tempering temperature of 300-400˚C, the absence of the phase distortion change indicates the emergence of additional factor in strengthening the metal from the formation of sub-boundaries and the dispersion strengthening from the carbide particles. Practical value. The given explanation of the mechanism of structural transformations in the process of tempering in the average temperature range of the hardened carbon steel can be used to optimize the technology of thermal strengthening of rolled metal.